THE INFLUENCE OF ARABIC SOUNDS ON ENGLISH PRONUNCIATION PRACTICED BY INDONESIAN QURAN TEACHERS - Gusti Lena Nurlaini; Ayunita Leliana (Jurnal Al-Fawa'id : Jurnal Agama dan Bahasa, 2022)
Three English fricatives [θ], [ð], and [ʃ] have been confusing many Indonesian people when they pronounce English words. Even though these three sounds are not present in Indonesian, they are found in Arabic. The goal of the research is to reveal if Indonesian Muslims, who are qualified Quran teachers, are able to pronounce English words correctly. The subjects of the research are passive English speakers but still get enough English exposure at college. In order to explore the language phenomenon, qualitative method is applied in this research. Qualitative method is used to describe and clarify experiences in people’s lives. From 60 data involving two subjects, the research showed that the two subjects succeeded in pronouncing 53 English words in total accurately. This phenomenon occurs due to a positive language transfer because Arabic can facilitate them to pronounce some English sounds.